STABILISE TECHNIQUE FOR TREATMENT OF TYPE B AORTIC DISSECTION: A LITERATURE REVIEW - Lopes, Alice (2019)
Endovascular techniques are currently the treatment of choice for complicated type B aortic dissection (cTBAD). Among them is the STABILISE technique, which goal is to achieve, in a single surgical time, an immediate remodeling of the thoraco-abdominal aorta with consequent obliteration of the false lumen through the reaposition of the dissection flap to the outer layers of the aorta. This is a relatively recent technique, with few published series. Therefore, this review aims to systematize the information to date on this technique of increasing importance in the treatment of acute type B aortic dissections.